Determination of chemical constituents in the leaves of Murraya Koenigh / Nurul Azwin Usol Ghafli - Usol Ghafli, Nurul Azwin (Faculty of Applied Sciences, 2009)
Phytochemical study on the leaves of Murraya Koenigii obtained from the Baling, Kedah has been conducted. The leaves were extracted with hexane as solvent yielding 2.918% of crude extract of dry weight. The crude extract (20.Og) was subjected to chromatographic method in order to separate and isolate the compound. The structure of the compound was determined by means of the Gas Chromatography-Mass Spectrum (GC-MS), Fourier Transform Infrared (FTIR) and *H and l C Nuclear Magnetic Resonance (NMR). Two compounds identified as murrayanine as one of the carbazole alkaloid and a mixture of sterols which are sitosterol, campesterol and stigmasterol has been isolated.